(untitled) (Canadian Journal of Counselling and Psychotherapy, 2018)
This article presents a qualitative study employing hermeneutic phenomenology to explore the experience of 4 counsellors using mindfulness to practice acceptance in their therapeutic work with clients. Findings are presented as four themes that demonstrate counsellors’ practices of acceptance: recognizing, allowing, attending to the physical, and experiencing the self and accepting clients. The findings suggest that accepting clients involves the intrapersonal process of accepting our experiences of clients—a practice honed through the self-cultivation of particular qualities and attitudes. The findings have implications in counsellor training and highlight the importance of self-cultivation for counsellors.